Metode Debat dalam Pembelajaran Sejarah Kebudayaan Islam di Madrasah Aliyah Pondok pesantren Al-Ikhlas Ujung Kabupaten Bone - Rajab, H. Abdul (JURNAL AL-QAYYIMAH, 2018)
This paper examines the learning about the history of Islamic culture at the Madrasah Aliyah Al-mukmin Sincere tip of Bone Regency by using the method of debate, the results showed that the method gives better influence debate if compared to learning that using conventional methods. This study gives a great effect from the results of the use of the method of debate which gives influence significance against the ability to understand in depth against learning the history of Islamic culture. A barrier to the implementation of the method of debate in Madrasah Aliyah Al-Ikhlas ends of Bone Regency is sometimes on students who are less aggressive in looking for material related to the study argued. Regarding the enhancement of learner achievements after the application of the learning system using the method of debate to the study of history of Islamic culture in the Madrasah Aliyah Al-Ikhlas ends of Bone Regency seen from the results of this research. In class experiments using the method of debate increased result compared to a control class that is 90% to 85%, while the control class only got 70% to 85%.